2021
DOI: 10.15625/2615-9023/16143
|View full text |Cite
|
Sign up to set email alerts
|

\(\textit{In vitro}\) antioxidant, α-amylase and α-glucosidase inhibitory activities of endophytic bacteria from the roots of the mangrove plant \(\textit{Rhizophora stylosa}\) Griffith

Abstract: Mangrove is one of the highly productive ecosystems and contains diverse plants and microbial communities. Bacterial endophytes from mangroves are considered as a prolific source of biological molecules with important functions in the protection of mangrove plants against herbivores, insects as well as pathogens. The present study aimed to isolate endophytic bacteria from the roots of mangrove plant Rhizophora stylosa and to screen antioxidant,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the present study, twenty-three endophytic bacteria belonging to nine genera (i.e., Microbulbifer , Streptomyces , Bacillus , Rossellomorea , Micrococcus , Paracoccus , Microbacterium , Pseudovibrio , and Brevibacterium ) were isolated from the fresh roots of R. apiculata . Previous investigations revealed that the genera Bacillus , Streptomyces , and Pseudovibrio have been isolated frequently from mangrove plants, whereas Microbulbifer , Micrococcus , Paracoccus , Microbacterium , and Brevibacterium have been isolated less frequently [ 10 , 70 , 71 , 72 , 73 ]. Genome analyses of the genera Bacillus , Streptomyces , and Pseudovibrio have reported that genomes of these genera contain versatile and diverse genes of metabolic pathways as well as genes linked to symbiosis and lifestyles, allowing for host switching and adapting to various environments [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, twenty-three endophytic bacteria belonging to nine genera (i.e., Microbulbifer , Streptomyces , Bacillus , Rossellomorea , Micrococcus , Paracoccus , Microbacterium , Pseudovibrio , and Brevibacterium ) were isolated from the fresh roots of R. apiculata . Previous investigations revealed that the genera Bacillus , Streptomyces , and Pseudovibrio have been isolated frequently from mangrove plants, whereas Microbulbifer , Micrococcus , Paracoccus , Microbacterium , and Brevibacterium have been isolated less frequently [ 10 , 70 , 71 , 72 , 73 ]. Genome analyses of the genera Bacillus , Streptomyces , and Pseudovibrio have reported that genomes of these genera contain versatile and diverse genes of metabolic pathways as well as genes linked to symbiosis and lifestyles, allowing for host switching and adapting to various environments [ 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plates were incubated at 30 °C for 3–5 days. After incubation, colonies with different morphological characteristics (e.g., color, shape, and consistency) were streaked on nutrient agar plates (NA, Himedia, Mumbai, India) to obtain the pure isolates [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were identified as Bacillus , Streptomyces and Pseudomvibrio . The ethyl acetate extracts of five isolated strains showed inhibitory activities against α-amylase with values ranging from 31.4 ± 3.1% to 59.7 ± 6.4% ( Dat and Thuy, 2021 ). Further, Dat et al (2022) investigated an endophytic Bacillus sp.…”
Section: Inhibitors Of Glycosidases From Different Microbesmentioning
confidence: 99%